The Impact of Direct Foreign Investment on the Economic and Social Development of Uzbekistan - Jurakulovna, Jumayeva Gulruh (International Journal of Psychosocial Rehabilitation, 2020)
This article examines the positive impact of foreign direct investment on the social sphere. Over the last 3 years, the share of fixed capital investment and foreign investment in it has been dynamically analyzed on the basis of statistics, and the main methodology of the study is how much these funds have increased the real money in the hands of the population. The main topic of the article is a comparative analysis of investment and social processes in the context of Uzbekistan, revealing the interrelationships. In addition, special attention will be paid to the significant socio-economic changes that have taken place in the country's economy in recent years.